2012
DOI: 10.1167/iovs.11-8724
|View full text |Cite
|
Sign up to set email alerts
|

Depletion ofSLC4A11Causes Cell Death by Apoptosis in an Immortalized Human Corneal Endothelial Cell Line

Abstract: Our data suggest that the reduction of cell number with time in SLC4A11-depleted HCECs is due to an increase in cell death by apoptosis. This suggests that SLC4A11 is necessary for cell survival and may explain the pathologic corneal endothelial cell loss in endotheliopathies due to SLC4A11 mutations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
2
33
0
Order By: Relevance
“…20,22 Moreover, it was recently shown that the knock-down of SLC4A11 causes a reduction of cellular growth and proliferation in HeLa cells and that a depletion of the SLC4A11 gene alone may already lead to apoptosis induction in CECs. 25,26 Prostaglandin-endoperoxide synthase 2 (PTGS2, COX2) was further evaluated in the early-onset FECD mouse model and in human late-onset FECD. PTGS2 was chosen due to its 5-fold endothelial transcriptional up-regulation in mutant animals, the previously established corneal endothelial expression of cyclooxygenases and its modulation capability with readily available drugs like COX2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…20,22 Moreover, it was recently shown that the knock-down of SLC4A11 causes a reduction of cellular growth and proliferation in HeLa cells and that a depletion of the SLC4A11 gene alone may already lead to apoptosis induction in CECs. 25,26 Prostaglandin-endoperoxide synthase 2 (PTGS2, COX2) was further evaluated in the early-onset FECD mouse model and in human late-onset FECD. PTGS2 was chosen due to its 5-fold endothelial transcriptional up-regulation in mutant animals, the previously established corneal endothelial expression of cyclooxygenases and its modulation capability with readily available drugs like COX2 inhibitors.…”
Section: Discussionmentioning
confidence: 99%
“…In CHED2 and FECD patients, there is a gradual reduction in endothelial cell number in addition to loss of function [Klintworth, 2009;Liu et al, 2012]. Accumulation of ER-retained proteins, in some cases, leads to apoptotic cell death [Xu et al, 2005].…”
Section: Expression Of Slc4a11 Mutants Does Not Induce Apoptosis or Cmentioning
confidence: 99%
“…41 Mutant SLC4A11 does not induce apoptosis in HEK293 cells on its own. 27 One report found that HEK293 cells transfected with mutant SLC4A11 decrease expression of antioxidant proteins, rendering the cells more susceptible to oxidative stress.…”
mentioning
confidence: 94%
“…38 Human SLC4A11 was originally reported to be a Na þ -coupled borate transporter, 37 but other groups have not been able to replicate this finding. 39,40 Instead, SLC4A11 has been found to facilitate Na þ /OH À transport, 41 NH 3 /H þ cotransport, 42 and electrogenic H þ (OH À ) permeation. 43 Human SLC4A11 mediates water movement when expressed in Xenopus laevis oocytes and HEK293 cells, 44 which makes it the first identified water transporter that is not a member of the major intrinsic protein family.…”
mentioning
confidence: 99%